2021
DOI: 10.3389/fped.2021.671107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNA Profiles and the Regulatory Network in Congenital Pulmonary Airway Malformations

Abstract: Background: Specific diagnostic markers for congenital pulmonary airway malformations (CPAMs) have not yet been discovered. This study intends to detect differentially expressed miRNAs in type I and type II CPAMs by using a miRNA chip and clarify the feasibility of miRNAs as different CPAM typing markers.Methods: Lung tissues of type I and type II CPAMs were collected and used to assess the differentially expressed miRNAs using a miRNA chip after evaluation using hematoxylin–eosin staining and Masson staining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this study, we set out to explore the role of miRNAs in the pathology of CPAM, a congenital disorder of the lung. Zeng et al [13] previously provided genomic insights into this 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we set out to explore the role of miRNAs in the pathology of CPAM, a congenital disorder of the lung. Zeng et al [13] previously provided genomic insights into this 10…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), which are highly conserved short noncoding RNA molecules, play an essential role in the onset and progression of lung diseases [9,10] by regulating a variety of biological functions, including cell differentiation and proliferation and organ morphogenesis [11,12]. The expression and role of miRNAs in CPAM were recently reported in a recent study by Zeng et al [13], who identified differentially expressed miRNAs in CPAMs, using miRNA chip analysis, in patients with CPAM. Specifically, the authors reported upregulation of miR-4523 and miR-548au-3p and downregulation of miR-21-3p, miR-590-3p, and miR-146a-3p in patients with type I-II CPAM compared with adjacent lesion tissue.…”
Section: Introductionmentioning
confidence: 99%
“…32 Moreover, hsa-miR-32-5p and miR-98-3p, also targeting RAB14, were identified as crucial lung cancer-associated miRNAs, [33][34][35] and their deregulation levels were identified in several respiratory disorders, such as acute respiratory distress syndrome, 36,37 bronchopulmonary dysplasia, 38 and congenital pulmonary airway malformations. 39 Besides, these miR-NAs have been previously related with viral processes. For instance, miR-32-5p has a significant regulatory role in avian hepatitis A viral infection, 40 visna maedi virus, 41 and caprine arthritis encephalitis viruses, 41 while the deregulation of the expression miR-98 has been described in a mouse model of West Nile virus neuropathogenesis.…”
Section: Discussionmentioning
confidence: 99%